2020
DOI: 10.3390/catal10050527
|View full text |Cite
|
Sign up to set email alerts
|

A DFT Insight into the Tuning Effect of Potassium Promoter on the Formation of Carbon Atoms via Carburization Gases Dissociation on Iron-Based Catalysts

Abstract: The research of the formation mechanism of iron carbides is significant to design the high-performance catalysts for the Fischer–Tropsch synthesis (FTS) process. In this paper, the effect of potassium promoter on the formation of atomic carbon via carburization gases dissociation on the iron-based catalyst, the C2H4, C2H2 and CO/H2 adsorption energies and dissociation paths as well as the rate constants of the corresponding elementary steps are investigated by DFT on the Fe(110), Fe(110)-K2O, Fe(211) and Fe(21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The electron-donating nature of potassium species causes local electron enrichment around the surface iron oxide sites, making them more difficult to be reduced . It is worthwhile to mention that alkali metal oxides such as K 2 O and Na 2 O are usually adopted in previous studies as the model compounds for theoretical calculations. , Although these alkali metal oxides are not present under the practical CO 2 hydrogenation reaction conditions, the alkali metal ions should still exhibit strong electron-donating capability. We also investigated a K 2 CO 3 cluster on the Fe 3 O 4 (111) surface and found a similar electron-donating effect.…”
Section: Resultsmentioning
confidence: 99%
“…The electron-donating nature of potassium species causes local electron enrichment around the surface iron oxide sites, making them more difficult to be reduced . It is worthwhile to mention that alkali metal oxides such as K 2 O and Na 2 O are usually adopted in previous studies as the model compounds for theoretical calculations. , Although these alkali metal oxides are not present under the practical CO 2 hydrogenation reaction conditions, the alkali metal ions should still exhibit strong electron-donating capability. We also investigated a K 2 CO 3 cluster on the Fe 3 O 4 (111) surface and found a similar electron-donating effect.…”
Section: Resultsmentioning
confidence: 99%
“…After recovering the K enrichment on the catalyst surface, all of the characteristic values in the FTS performance were fully restored to normal. These variation trends exactly demonstrated that the K promoter was a key factor in influencing the trends of FTS product selectivity, which restricted the secondary hydrogenation of alkenes and led to more formation of light olefins and long-chain hydrocarbons [52,53]. denoted as Fe@C-1.0-W, with a K residual of 0.1 wt% (Table 4).…”
Section: Catalytic Performance Of Fischer-tropsch Synthesismentioning
confidence: 76%
“…After recovering the K enrichment on the catalyst surface, all of the characteristic values in the FTS performance were fully restored to normal. These variation trends exactly demonstrated that the K promoter was a key factor in influencing the trends of FTS product selectivity, which restricted the secondary hydrogenation of alkenes and led to more formation of light olefins and long-chain hydrocarbons [52,53]. Overall, one extremely facile, green, low-cost synthetic strategy of high-performance FTS catalysts was successfully explored to in situ construct K-Fe3C@C nanohybrids by using only ferric nitrate and pomelo peel without chemical pretreatment.…”
Section: Catalytic Performance Of Fischer-tropsch Synthesismentioning
confidence: 84%
“…To obtain full carburization, H 2 is needed to remove oxygen coming from CO dissociation as H 2 O. Such reactions can be favored by opportune doping: in particular, potassium doping favors CO dissociation on iron and its carburization [246]. Also, cobalt can be carburized to CoC 2 using pure CO at 490-500 K, while only partial carburization occurs using syngas [142,247].…”
Section: The Adsorption and Activation Of Comentioning
confidence: 99%